2020
DOI: 10.18203/2349-3933.ijam20202592
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of 3 tests of cognitive impairment MMSE, AD-8, GPCOG in 200 geriatric cases suspected to have cognitive impairment out of 3750 screened

Abstract: Background: Dementia is a progressive decline in cognition, function, behavior and activities of daily living. Many assessment scales are used in screening for cognitive impairment, making diagnosis of dementia and for follow-up. Assessment scales in the domains of cognition, function, behavior, quality of life, depression in dementia, care giver burden and dementia severity are used. There are many tools used to assess cognitive function.Methods: Authors performed the 3 object recall, 3 name recall tests, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…When compared to the MMSE, the GPCog has been shown to have increased sensitivity [ 24 ]. A study of 3750 geriatric patients previously identified 68% as requiring further testing, and of those 49% went on to have a diagnosable dementia [ 25 ]. Of the ‘false positives’ in that study, 38% showed signs of definitive cognitive impairment that did not meet diagnostic criteria [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to the MMSE, the GPCog has been shown to have increased sensitivity [ 24 ]. A study of 3750 geriatric patients previously identified 68% as requiring further testing, and of those 49% went on to have a diagnosable dementia [ 25 ]. Of the ‘false positives’ in that study, 38% showed signs of definitive cognitive impairment that did not meet diagnostic criteria [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of 3750 geriatric patients previously identified 68% as requiring further testing, and of those 49% went on to have a diagnosable dementia [ 25 ]. Of the ‘false positives’ in that study, 38% showed signs of definitive cognitive impairment that did not meet diagnostic criteria [ 25 ]. These findings suggest that those with mild signs of impairment are most likely to be deemed as not requiring further care as well as more likely to reject specialist support.…”
Section: Discussionmentioning
confidence: 99%